Time-varying Mesh Stiffness Calculation of Planetary gear based on Improved Energy Method - Zhang Huiling (Jixie chuandong)
The time-varying meshing stiffness is an important parameter of the planetary gear failure mechanism. In considering the relationship between the base circle and the dedendum circle under the condition of the number of teeth for parameters,an improved model of cantilever beam is established. For each pair of planetary gear meshing time-varying meshing stiffness are discussed,considering the wheel body stiffness,energy method is applied to solve more accurate tooth meshing stiffness. On the basis of this method,the timevarying meshing stiffness of sun wheel,planetary wheel and internal ring gear when crack exists in each pair in meshing is calculated and the effects of crack depth and angle on time-varying meshing stiffness are explored.The research provides theoretical help for the mastery of planetary gear fault mechanism.